The friction of tilted skates on ice - van Leeuwen, J. M. J. (2019)
The friction felt by a speed skater is calculated as function of the velocity and tilt angle of the skate. This calculation is an extension of the more common theory of friction of upright skates. Not only in rounding a curve the skate has to be tilted, but also in straightforward skating small tilt angles occur. The tilt increases the friction substanstially and even for small tilts the increase is relevant. The increase of the friction with the velocity, which is very slow for the upright skate, becomes more pronounced for large tilts.